Pengembangan Video Pembelajaran Berbasis Kearifan Lokal Pada Pelajaran TIK di Kelas VII Sekolah MTs Ar-Rahman Wampu - Muhammad Fajar Salim Suriyono; Syaiful Bahri; Ade Evi Fatimah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to develop and assess the effectiveness of locally wisdom-based instructional videos on computer hardware topics for seventh-grade students at MTs Ar Rahman Wampu, Langkat Regency, North Sumatra. The research method employed is developmental research, utilizing the 4-D model proposed by Thiagarajan, encompassing the stages of defining, designing, developing, and disseminating. The study is conducted at MTs Ar Rahman Wampu over a two-month period, with seventh-grade students randomly selected as research subjects. The object of the study is the instructional video based on local wisdom concerning computer hardware. Research instruments include a video validation sheet, student activity observation sheet, and questionnaires measuring student responses and learning interests. Data analysis involves evaluating the validity, practicality, and effectiveness of the instructional video, utilizing percentages and predefined criteria. The subsequent practicality analysis incorporates expert assessments and field observations. The effectiveness of the learning process is assessed through student tests, percentage of activity time, and positive responses to the instructional video. The enhancement of learning interest is measured through normalized gain calculations. The expected outcome of this research is to contribute to the development of innovative and high-quality instructional videos within the context of local wisdom, especially in the field of ICT education at the MTs level. Keywords: Instructional Video, Local Wisdom, Instructional Development